Development of a Flipbook Pantun Based on the Think Talk Write Model to Improve the Writing Skills of Fifth-Grade Elementary School Students - Ayu Lupinatarita Primadani, Diah; Dewi Purwati, Panca (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2025)
This study is dedicated to enhancing the Pantun writing skills of high-grade elementary students through developing and evaluating digital teaching materials in a flipbook format. The research follows the development model outlined by Sugiyono. The product was validated by media and material experts, who provided feedback that reflected a high level of appropriateness. The media experts rated the materials at 95%, categorizing them as very feasible based on their alignment with learning objectives, design, language, and usability. The material expert assigned a score of 81%, also within the very feasible category, considering the relevance of content, language, and presentation. The feasibility test results from a small-scale trial indicated a 100% approval rate from educators and a 90.41% positive response from students. Pretest scores averaged 52.76, which rose significantly to 88.80 in the posttest, demonstrating a substantial improvement of 36.04 points. The n-gain test results were 77.42 for the small scale and 76.93 for the large scale. These findings substantiate that developing the Pantun flipbook, grounded in the think-talk-write model, is highly feasible and effective in enhancing students' writing Pantun. This innovative learning strategy not only aids in developing writing skills but also fosters critical thinking, discussion, and expressing ideas in written form.